Optimization of Mosques, Madrasahs and Islamic Boarding Schools in Eradicating Illiteracy with the Reflect Method in Pamayangsari Hamlet, Cikawungading Village, Tasikmalaya Regency - Ami Abdullah Fahmi; Naufal Hibban Firdaus; Ilham Nur Rohman; Fazri Agus Setiawan; Rizky Maulana; Opan Sopandi; Arya Nugraha (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This article aims to describe the condition of illiterate children in Pamayangsari Hamlet, and the application of the reflect method in alleviating illiteracy. This article uses descriptive analytic method with data collection through interviews and observations to the community. At the observation stage, the problem of illiteracy was found in children aged 6-12 years. During implementation, empowerment is carried out in mosques and madrasas. The next stage is awareness, where the community is educated about the importance of literacy. Activities are carried out in an interesting way so that children are more likely to like them, such as competitions and other educational activities. The last program is action, focusing on direct teaching to overcome illiteracy. Evaluation is done through observation, community enthusiasm and assessment of children's literacy skills. In conclusion, the reflect method yielded significant results in alleviating illiteracy.